The Values of Integration-Interconnection in the Material of Arabic Textbook for Islamic Senior High School in Indonesia - Muhammad Sya'dullah Fauzi; Zaimatuz Zakiyah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2021)
As one of the scientific disciplines in the sociolinguistic field, Arabic is often only fixated on the concept of language without involving other scientific studies, thus giving birth to Arabic learners who are less responsive to the times. This study aims to analyze the values of integration-interconnection contained in the material in the Arabic textbook class XII Islamic Senior High School published by the Indonesian Ministry of Religion, supported by other relevant documents using a literature study. The data collected in the field were analyzed using descriptive-qualitative. This study indicated that the five chapters has already contained the value of integration-interconnection between religious, scientific, and social sciences. However, there were no value in scientific knowledge found in Chapter II and III. Also, the result of this study needed to be emphasized the application of the value of integration-interconnection in Arabic learning. It is not enough to rely only on textbooks alone, but it also requires the presence of teachers who participate in extracting other scientific values. The results are expected to contribute to improving the concept of Arabic textbooks, which contain the value of integration-interconnection. Further research is expected to explore the value of integration-interconnection at every level of education.